Solid state thermal decomposition of amide complexes of nickel(II) chloride - Nelwamondo, Aubrey Ndifelani (Rhodes University, Faculty of Science, Department of Chemistry, 1997)
The thermal decompositions of a series of amide complexes of nickel(II) chloride have been studied. Thermochemical, kinetic, structure and solid-state stability correlations have been investigated. Complexes containing homologous amide ligands (L) of the form NiLCℓ₂, Ni₃L₂Cℓ₆, Ni₃LCℓ₆, NiL₂Cℓ₂(2H₂0) and ML₂Cℓ₂ (where M = Ni(II), Co(II) or Cu(II)) have been prepared. Chemical analysis, spectral and thermogravimetric measurements were used to characterize the complexes and their decomposition stoichiometries. Three sets of reactions were identified as yielding stable products in a single step: (i) NiLCℓ₂ (s) → NiCℓ₂ (s) + L (g) (ii) Ni₃LCℓ₆ (s) → 3NiCℓ₂ (s) + 2L (g) (iii) Ni₃LCℓ₆ (s) → 3NiCℓ₂ (s) + L (g) Characterization of the processes in the ML₂Cℓ₂ and NiL₂Cℓ₂(2H₂0) complexes was not straightforward. Reaction enthalpies (ΔH) were determined using DSC. The orders of the reaction onset temperatures (Tc), peak temperatures (Tmax) and ΔHL values for the NiCℓ₂ system were: N-methylacetamide < acetamide < N-methylformamide, suggesting the importance of steric hindrance of the methyl-substituent groups in the amide skeleton. In the Ni₃LCℓ₆, NiL₂Cℓ₂(2H₂0) and ML₂Cℓ₂ systems no simple orders could be deduced. The Te and Tmax sequences obtained from analogous metal(II) chloride complexes indicated that the copper(II) complexes were the least stable. The kinetics of the loss of L from NiLCℓ₂ complexes were investigated using isothermal TG, non-isothermal TG and DSC measurements. The contracting geometry models described the course of the decompositions in the most satisfactory manner. Apparent activation energies ( Ea) were estimated from Arrhenius plots of rate coefficients from: (i) an approximate zero-order relationship, (ii) the contracting-area (R2) and contracting-volume (R3) equations, (iii) a new empirical (B2) expression, (iv) the half-life ( 1/t₀.₅) and (v) the characteristic feature of the rate-time curve ( 1/tmax/2 ). The non-dependence of Ea on the rate equation used supports the reliability of the kinetic parameters. Non-isothermal experiments were analyzed by the Coats-Redfern, the modified BorchardtDaniels and the Kissinger methods. Arrhenius parameters were in keeping with results from the isothermal kinetic measurements. The values of Ea obtained for the NiLCℓ₂ system increased with an increase in basicity of the amide ligands. No straightforward correlation was found between Ea and Te, Tmax, ΔHL or spectral properties.
Keywords: Decomposition (Chemistry); Materials -- Thermal properties; Amides